Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T20:37:50+01:00
A) f(x) = (1- sin⁴x - cos⁴x)/(1 - cos²x - sin⁶x)

dziedzina:
1 - cos²x - sin⁶x ≠ 0
sin²x - sin⁶x ≠ 0
sin²x(1 - sin⁴x) ≠ 0
sin²x(1 - sin²x)(1 + sin²x) ≠ 0
sin²x(1 - sinx)(1 + sinx)(1 + sin²x) ≠ 0
1 + sin²x > zawsze

sinx ≠ 0 i sinx ≠ 1 i sinx ≠ - 1
x ≠ kπ/2; k ∈ Z

zbiór wartości:
można skrócić przez sin²x*cos²x, bo dziedzina:
f(x) = (1- sin⁴x - cos⁴x)/(1 - cos²x - sin⁶x) = f(x) = (sin²x + cos²x - sin⁴x - cos⁴x)/sin²x(1 - sin²x)(1 + sin²x) = (sin²x(1 - sin²x) + cos²x(1 - cos²x))/sin²x(1 - sin²x)(1 + sin²x) = 2*sin²x*cos²x/sin²x*cos²x*(1 + sin²x) = 2/(1 + sin²x)

1 ≤ 1 + sin²x ≤ 2
1 ≥ 1/(1 + sin²x) ≥ 1/2
2 ≥ 2/(1 + sin²x) ≥ 1
2 ≥ f(x) ≥ 1
Zw: <1, 2>

b) f(x) = 4sin²x - 4sinx + 5

D = R
4sin²x - 4sinx + 5
t = sinx, t ∈ <-1, 1>
f(t) = 4t² - 4t + 5
f(- 1) = 4 + 4 + 5 = 13
f(1) = 4 - 4 + 5 = 5

Zw: <5, 13>
jak masz pytania to pisz na pw